STRATEGIC APPROACHES TO JUSTIFY STRATEGIES FOR SUCCESSFUL DEVELOPMENT OF BANK INSTITUTIONS TAKING INTO ACCOUNT ECONOMIC AND INSTITUTIONAL FACTORS - I. Konovalova; E. Gorlova; D. Shepelev (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the parameters of creating the right banking strategy, features and factors, A constructive strategy for the economic behaviour of the banking system in the economic market, Analysis of approaches to establishing the stability of financial organizations and structural components of their financial location, The nuances of economic stability of banking institutions as conditions of competitiveness are investigated, conditions are identified, Positively and negatively affecting financial stability offinancial institutions, the distinctive characteristics of functional expectations of various participants of financial and credit relations for financial stability and stability are touched upon.